Modulating effect of mitomycin or cisplatin on lymphokine-activated killer cell proliferation and antitumor activity to bladder cancer cell lines in vitro - Wang Zhi-Ping; Qing Da-Shan; Shi Bao-Guang; Chen Yi-Rong; Liu Guo-Dong (Acta Pharmacologica Sinica; Vol 19, No 4 (July 1998): Acta Pharmacologica Sinica, 2016)
AIM: To study the effect of mitomycin (Mit) or cisplatin (Cis) on the proliferation of lymphokine-activated killer (LAK) cells in patients with transitional cell cancer of bladder and their cytolysis to bladder tumor cells. METHODS: LAK cell proliferation was assayed in the presence of Mit or Cis by cell counting. Bladder cancer cell lines BIU-87 and EJ were cultured as target cells and cytotoxicity of LAK cells was determined by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. RESULTS: The proliferation of LAK cells induced by recombinant interleukin-2 (IL-2) was inhibited by Cis in a concentration-dependent manner and was decreased to 55.3% at 100 mg.L-1 compared with control at 96 h. The enhanced growth of the LAK cells was observed with Mit 5-10 mg.L-1 from 48 to 96 h. Cis 10 mg.L-1 increased the cytotoxicity against BIU-87 and EJ cells. CONCLUSION: Immunomodulatory effect of chemotherapeutic agents on LAK cell proliferation induced by IL-2 in patients with bladder cancer mainly depends on the drug itself.